Comparison of Postpartum Depression Treatments in Different Country Income Groups: A Literature Review - Manik, Andrea Valerie; Humairah, Ira; Lauric, Kelsey (Journal of Community Medicine and Public Health Research, 2025)
Postpartum depression remains a major global public health issue, with significant prevalence worldwide, in both low- and high-income countries. Postpartum depression not only affects the mother but also has detrimental effects on the infant. Despite this, it remains a neglected topic, with a lack of treatment services provided, especially in low and lower-middle-income countries. This study aims to compare treatment approaches across highand low-income countries, identify variations in their approaches, and determine the most effective treatment options for each country's income group, particularly low-income countries. This study’s method employs a literature review to inform the survey's outcome, drawing on previous research that each discussed multiple postpartum depression treatments. It was found that there was a difference in each country's income group’s approaches, specifically in the use of antidepressants in high-income countries and more common psychological and psychosocial interventions in low-income countries. However, this does not mean that psychosocial methods are lacking; in fact, some research indicates that this approach is more effective for patients. Therefore, low-income countries should implement psychological and psychosocial interventions more commonly to ensure the prevalence of postpartum depression decreases, as well as to prevent any adverse effects it may have on both mothers and infants.